EFEKTIVITAS PELATIHAN MEDITASI PERNAFASAN DALAM MENURUNKAN TINGKAT STRES PADA PENDUKUNG SEBAYA ODHA - Fella Fendina; Fuad Nashori; Indahria Sulistyarini (Jurnal Psikologi Integratif, 2018)
Stress is particularly at risk for physical condition, psychological, and productivity of ODHA's peer support. This research aims to determine the effectiveness of breathing meditation training to reduce stress level on ODHA's peer support. The research was conducted at Yogyakarta X foundation on 14 peer supporters which divided into two groups, namely group of experimental and group of control. This research used Quasi Experimental Pretest-Posttest Control Group Design. Research data will be analyzed using ANAVA MIX statistical technique. The result showed there was a significant differentiation between the experimental group and the control group. From this research also known that the Effect Size of breathing meditation training on stress decrease equal to 64%. Thus it can be stated that breathing meditation training is effective in reducing stress on peer support of ODHA. Keywords : Stress, Breathing Meditation, Peer Support of ODHA